2019
DOI: 10.3389/fphar.2019.00346
|View full text |Cite
|
Sign up to set email alerts
|

NUDT15 Polymorphism Confer Increased Susceptibility to Thiopurine-Induced Leukopenia in Patients With Autoimmune Hepatitis and Related Cirrhosis

Abstract: The aim of this study was to investigate the influence of NUDT15 R139C and thiopurine S-methyltransferase ( TPMT ) on azathioprine (AZA) induced leukopenia in patients with autoimmune hepatitis (AIH) and related cirrhosis. A total of 149 Chinese AIH patients with a history of AZA treatment were retrospectively evaluated. The clinical and epidemiological characteristics of the patients were obtained from an electronic database and reviewed. NUDT15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 33 publications
5
22
1
Order By: Relevance
“…29 The frequency we observed in this study was 12.4%, which is the same as the frequency of 9.4% in AIH patients reported by Xiaoli Fan et al. 19 Recent studies have found NUDT15 c.415C > T variants were associated with thiopurine-induced leukopenia, particularly in Asian populations. 26,30−32 In 2014, Yang et al 11 revealed for the rst time that NUDT15 c.415C > T allelic mutation is signi cantly associated with AZA-induced leukopenia in Korean IBD patients (P = 5.58 × 10 − 43 , OR = 8.61).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…29 The frequency we observed in this study was 12.4%, which is the same as the frequency of 9.4% in AIH patients reported by Xiaoli Fan et al. 19 Recent studies have found NUDT15 c.415C > T variants were associated with thiopurine-induced leukopenia, particularly in Asian populations. 26,30−32 In 2014, Yang et al 11 revealed for the rst time that NUDT15 c.415C > T allelic mutation is signi cantly associated with AZA-induced leukopenia in Korean IBD patients (P = 5.58 × 10 − 43 , OR = 8.61).…”
Section: Discussionsupporting
confidence: 88%
“…Subsequently, it was also con rmed in Japanese IBD patients that NUDT15 c.415C > T allele mutation is closely related to AZA-induced early leukopenia 13 (P = 1.92 × 10 − 16, OR = 28.4). The studies by Xiang Fei et al 29 and Xiaoli Fan et al 19 on Chinese autoimmune diseases and AIH patients also showed that NUDT15 c.415C > T SNP is signi cantly related to AZA-induced early leukopenia (P = 1.79 × 10 − 7 ; OR = 7.59 and P < 0.00001; OR = 20.41, respectively). Our result was concordant with previous studies, which showed NUDT15 c.415C > T allelic mutation was associated with early leukopenia (P = 8.26 × 10 − 7 ; OR = 7.5).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Aberrant autoimmunity is thought to induce an interaction between genetic susceptibility and unknown environmental triggers to cause persistent hepatocyte damage. Precision medicine for AIH, including diagnosis, medicinal therapy, and drug monitoring, is a novel therapeutic pattern distinct from evidence-based medicine that aims to develop a personalized treatment strategy (Bossen et al, 2018; Chen et al, 2019; Fan et al, 2019). However, ∼20% of AIH patients exhibit a poor response to standard treatment with glucocorticoids alone or in combination with azathioprine, and the number of effective second-line therapeutic options for AIH is limited (2015; Cropley and Weltman, 2017; Shen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%